Epidemiological trends in mortality, event rates and case fatality of acute myocardial infarction from 2004 to 2015: results from the KORA MI registry. (1st January 2021) - Krämer, Christina; Meisinger, Christa; Kirchberger, Inge; Heier, Margit; Kuch, Bernhard; Thilo, Christian; Linseisen, Jakob; Amann, Ute
Abstract: Aim: This study examines epidemiological trends of acute myocardial infarction (AMI) in Germany from 2004–2015 across different age groups, using data of the population-based KORA myocardial infarction registry. Methods: Annual age-standardised, age-group- and sex-specific mortality and event rates (incident and recurrent) per 100, 000 population as well as 28-day case fatality were calculated from all registered cases of AMI and coronary heart disease deaths in 25–74-year-olds from 2004–2015 and 75–84-year-olds from 2009–2015. Average annual percentage changes (AAPC) were calculated by joinpoint regression. Results: Mortality rates declined considerably among the elderly (75–84 years), in men by –6.0% annually, due to declines of case fatality by –3.0% and incidence rate by 3.4% and in women by –10.0%, driven by declines in incidence (–9.1%) and recurrence rate (–4.9%). Significant mortality declines also occurred in males, 65–74 years of age (AAPC –3.8%). Among the age groups 25–54 years and 55–64 years, there was no substantial decline in mortality, event rates or case fatality except for a decline of incidence rate in 55–64-year-old men (AAPC –1.8%). Conclusion: Inhomogeneous AMI trends across age-groups indicate progress in prevention and treatment for the population >64 years, while among <55-year-olds, we found no significant trend in AMI morbidity and mortality. KEY MESSAGES: Age standardised AMI mortality continued to decline from 2009 to 2015 in the study region. Declines in AMI mortality were driven by declines in event rates (both incidence and recurrence rates) and case fatality. AMI trends were inconsistent across different age groups with the strongest declines in mortality and event rates among the elderly population (75–84 years of age).